(untitled) (Journal for Freedom of Conscience (Jurnalul Libertății de Conștiință), 2022)
Social Entropy and Freedom of Conscience Social entropy is present in any closed system and in almost every known form of life. Usually social entropy is associated with chaos and disorder although neither chaos nor disorder can be clearly defined and identified. In this framework where disorder is statuary, freedom of conscience can acquire different values. The disorder does not create restraints but it offers various types of freedoms. Freedom of conscience is usually associated with the presence of an increased and respectable order. The social order (as opposed to the social entropy) demands the presence of structures at social level. The natural tendency of these structures is to limit the freedoms of the individual and to favor those of the community or in some cases over the objective ones. The apparent conflict between social entropy and freedom of conscience can be resolved by proposing a paradigm in which freedom of conscience, understood and objectively applied, can be an anti-entropic support.